ENTREPRENEURIAL INTENTION-BEHAVIOUR LINK: THE MODERATING EFFECTS OF COVID-19 PERCEPTION, ENTREPRENEURIAL MOTIVATION, AND PRIOR ENTREPRENEURIAL EXPOSURE - Hee Song Ng; Tit Yean Chiang; Daisy Mui Hung Kee (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Given the current economic challenges facing many developing countries across the globe, entrepreneurship has become the main goal to drive economic development. Thus, governments need to cultivate more future entrepreneurs and develop existing entrepreneurs’ abilities to drive job opportunities. This study aims to investigate the entrepreneurial intention–behaviour gap. It further examines the moderating effects of COVID-19 perception, entrepreneurial motivation, and prior entrepreneurial exposure on the moderated relationship between entrepreneurial intention and behaviour (action). Entrepreneurship has been widely studied to boost job creation and stimulate the domestic economy. Most studies have focused on entrepreneurial behaviour and new venture creation, drawing on widely tested Ajzen’s (2020) theory of planned behaviour (TPB). Entrepreneurial action is widely viewed as an intentionally planned behaviour. The formation of entrepreneurial intention can trigger entrepreneurial behaviour of actually starting up processes. The extant literature reveals that academic researchers consider the studies on the intention-behaviour link as an under-researched area (Alam, Kousar and Rehman, 2019). Hence, examining the link and testing whether the expanded TPB model holds for the Malaysia case makes sense. Although this model is widely tested empirically, new research regarding moderation effects may be valuable (Sabah, 2016). The most important three moderators are COVID-19 perception, entrepreneurial motivation, and prior entrepreneurial exposure, which will be tested to see if their presence moderates the relationship. This study is expected to support three moderators’ intention–behaviour link and moderation of this link (Kong, Zhao and Tsai, 2020). This will confirm (or disconfirm) the conventional wisdom that explains why some graduates with entrepreneurial intentions act when others do not. Theoretical and practical implications are discussed.